2006
DOI: 10.1002/ab.20147
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic costs of aggressive behaviour in the Siamese fighting fish,Betta splendens

Abstract: Aggressive conflicts between males are often resolved by means of multiple ritualized agonistic displays without damaging escalation. Apparently, in such cases by using those displays opponents exchange important motivational and physical information on which they base a decision to stay or leave the interaction. In the Siamese fighting fish, the time spent spreading the dorsal fin and erecting the gill coverts predicts who will be the winner or loser of the interaction. Two experiments were carried out to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
3
44
0
2
Order By: Relevance
“…Studies of alpha male descent in natural populations of primates have found that it occurs for many possible reasons, including the alpha male being no longer physically capable of staving off challenger males, alpha males losing coalitionary support, the immigration of more dominant individuals into the social group, or the sexual maturation of younger, more dominant individuals (O'Shea, 1976;Perry, 1998;Uehara et al, 1994). It is highly metabolically costly for alpha males to consistently defend their dominance status and territory through physical fighting (Briffa & Sneddon, 2007;Castro, Ros, Becker, & Oliveira, 2006;Rohwer & Ewald, 1981) and other behaviours such as scent marking (Gosling, Roberts, Thornton, & Andrew, 2000). Dominant alpha males of many species also have higher levels of testosterone and cortisol that may be physiologically damaging (Gesquiere et al, 2011;Higham, Heistermann, & Maestripieri, 2012;Mendonça-Furtado et al, 2014;Sapolsky, 2005).…”
Section: Formation and Maintenance Of Social Hierarchiesmentioning
confidence: 99%
“…Studies of alpha male descent in natural populations of primates have found that it occurs for many possible reasons, including the alpha male being no longer physically capable of staving off challenger males, alpha males losing coalitionary support, the immigration of more dominant individuals into the social group, or the sexual maturation of younger, more dominant individuals (O'Shea, 1976;Perry, 1998;Uehara et al, 1994). It is highly metabolically costly for alpha males to consistently defend their dominance status and territory through physical fighting (Briffa & Sneddon, 2007;Castro, Ros, Becker, & Oliveira, 2006;Rohwer & Ewald, 1981) and other behaviours such as scent marking (Gosling, Roberts, Thornton, & Andrew, 2000). Dominant alpha males of many species also have higher levels of testosterone and cortisol that may be physiologically damaging (Gesquiere et al, 2011;Higham, Heistermann, & Maestripieri, 2012;Mendonça-Furtado et al, 2014;Sapolsky, 2005).…”
Section: Formation and Maintenance Of Social Hierarchiesmentioning
confidence: 99%
“…For example, the ability to acquire and defend territories or engage in prolonged courtship displays should correspond with high physiological capacity of an individual. Aggressive interactions are energetically expensive (Castro et al. 2006) and require modifications of muscle tissue and metabolic capacity for extended displays.…”
Section: Hormones Morphs Performance and Behaviour – Consequences Omentioning
confidence: 99%
“…Energetic costs of sexual displays or signaling, as well as male‐male combat behaviors, have been shown across many species including fish (Castro et al. ; Ros et al. ), birds (Höglund et al.…”
mentioning
confidence: 99%